2022
DOI: 10.1371/journal.pone.0271500
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Community Assets Supporting Transitions (CAST) transitional care intervention for older adults with multimorbidity and depressive symptoms: A qualitative descriptive study

Abstract: Background Older adults with multimorbidity experience frequent care transitions, particularly from hospital to home, which are often poorly coordinated and fragmented. We conducted a pragmatic randomized controlled trial to test the implementation and effectiveness of Community Assets Supporting Transitions (CAST), an evidence-informed nurse-led intervention to support older adults with multimorbidity and depressive symptoms with the aim of improving health outcomes and enhancing transitions from hospital to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Some studies have reported positive impacts, while others have reported no or negative impacts [ 17 , 18 , 33 37 ]. Other studies found major implementation bottlenecks due to lack of resources, and information and organisational problems [ 38 , 39 ]. This is in line with our experience with the TCI implementation.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported positive impacts, while others have reported no or negative impacts [ 17 , 18 , 33 37 ]. Other studies found major implementation bottlenecks due to lack of resources, and information and organisational problems [ 38 , 39 ]. This is in line with our experience with the TCI implementation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Care transitions can be very challenging because they encompass the integration and coordination of care across different health care sectors and providers that are involved in the patient's circle of care. 6 Given that the complexity of transitional care may increase for older adults as they navigate the healthcare system, 7 and since their participation in decision-making during transitional care is sometimes missing, 8,9 the present study aimed to explore the perspectives of older adults and their healthcare providers on transitional care from hospital to cardiac rehabilitation during the COVID-19 pandemic, with a special focus on the patient decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…5 Care transitions can be very challenging because they encompass the integration and coordination of care across different health care sectors and providers that are involved in the patient's circle of care. 6…”
Section: Introductionmentioning
confidence: 99%